Comparing methods of transport in an age of social distancing - Cherai, Rime; Gayomali, Jonathan; Benítez, Nuria (My University, 2020)
This article explores the new urban mobility paradigm in an after COVID-19 world. The pandemic has dramatically changed the conditions under which users access and use public transportation. Analysing mobility in cities across the world – New York, Mexico City – the study highlights the dense demand for public transportation solutions in those two different megalopolises. The experience of COVID-19 pandemics has shed the light on the necessity of rethinking the current offer and creating a new set of adaptive solutions which replace sanitary safety as a central element of assessment. To what extent are COVID-19 and the possibility of other spreading of viruses affecting how common modes of transportation are thought about and used? The article revises first the modes of transportations. Emphasizing the unique challenge of social distancing imposed by the pandemic, the study covers its consequences for users, cities authorities as well as operators. While it appears as a condition to contain the spread of the virus, it is also part of an economic equation for operators, who might struggle soon to cover growing operational costs, while running their networks with a smaller number of travellers. Finally, the study opens the discussion on the opportunity offered by the pandemic to redesign and rethink our mobility more adaptively and sustainably.
Keywords: Design; Social Design; Social Change; Sustainability; Innovation; Technology; Social Enterprises; Social Awareness; Social Responsibility